"MUNSHAOT" - A MASTERPIECE OF UZBEK EPISTOLARY LITERATURE (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Examples of the epistolary genre based only on letters have also been created in modern Uzbek prose. Among these works, Alisher Navoi's work "Munshaot", Nizamiddin Alisher's justice, all his works society and raiyat, is fully reflected. "Munshaot" means essays, that is, letters. During the time of Timur and his followers, the correspondence between the society, the state and the citizens developed in a strange way due to the highly flourishing culture. With the exception of Alisher Navoi's work "Munshaot", all of the listed ones consist of letters or correspondence, as in Uzbek literature and world literature.